Individual Neurons Confined to Distinct Antennal-Lobe Tracts in the Heliothine Moth: Morphological Characteristics and Global Projection Patterns - Ian, Elena; Zhao, Xin C.; Lande, Andreas; Berg, Bente G. (Frontiers in Neuroanatomy, 2016)
To explore fundamental principles characterizing chemosensory information processing, we have identified antennal-lobe projection neurons in the heliothine moth, including several neuron types not previously described. Generally, odor information is conveyed from the primary olfactory center of the moth brain, the antennal lobe, to higher brain centers via projection neuron axons passing along several parallel pathways, of which the medial, mediolateral, and lateral antennal-lobe tract are considered the classical ones. Recent data have revealed the projections of the individual tracts more in detail demonstrating three main target regions in the protocerebrum; the calyces are innervated mainly by the medial tract, the superior intermediate protocerebrum by the lateral tract exclusively, and the lateral horn by all tracts. In the present study, we have identified, via iontophoretic intracellular staining combined with confocal microscopy, individual projection neurons confined to the tracts mentioned above, plus two additional ones. Further, using the visualization software AMIRA, we reconstructed the stained neurons and registered the models into a standard brain atlas, which allowed us to compare the termination areas of individual projection neurons both across and within distinct tracts. The data demonstrate a morphological diversity of the projection neurons within distinct tracts. Comparison of the output areas of the neurons confined to the three main tracts in the lateral horn showed overlapping terminal regions for the medial and mediolateral tracts; the lateral tract neurons, on the contrary, targeted mostly other output areas in the protocerebrum.